Branch Banking in California and Bank Failures - Wernette, John Philip (Quarterly Journal of Economics, 1932)
Journal Article Branch Banking in California and Bank Failures Get access John Philip Wernette John Philip Wernette Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 46, Issue 2, February 1932, Pages 362–375, https://doi.org/10.2307/1883235 Published: 01 February 1932